2018
DOI: 10.14202/vetworld.2018.895-901
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of Newcastle disease antibody as a reagent to develop a rapid immunodiagnostic test tool

Abstract: Aim:This research was conducted to produce and characterize ND antibody as reagent candidate to develop a rapid immunodiagnostic test tool.Materials and Methods:Four New Zealand White rabbits were used in this study and divided into two groups. First group was injected by Sato ND antigen, and second group was injected by genotype VII ND antigen. This study is divided into three steps: (a) ND antibody production, (b) ND antibody purification, and (c) ND antibody characterization. First group was rabbit injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Samiullah et al [ 28 ] produced an antibody for APMV-1 using adjuvant within 91 days and reach a 1024 (2 10 ) HI titer with 4 and 5 injections. Putri et al [ 29 ] produced antibodies to Newcastle disease in New Zealand rabbits with subcutaneous route application for the first and second injection, which resulted in the same pattern of antibody titer until the 16th day after the second injection. Moreover, after the third injection intravenously, the study revealed a higher antibody titer on the 8th day, reaching HI titer of 2 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Samiullah et al [ 28 ] produced an antibody for APMV-1 using adjuvant within 91 days and reach a 1024 (2 10 ) HI titer with 4 and 5 injections. Putri et al [ 29 ] produced antibodies to Newcastle disease in New Zealand rabbits with subcutaneous route application for the first and second injection, which resulted in the same pattern of antibody titer until the 16th day after the second injection. Moreover, after the third injection intravenously, the study revealed a higher antibody titer on the 8th day, reaching HI titer of 2 9 .…”
Section: Resultsmentioning
confidence: 99%
“…According to Putri et al . [20], antibody production in laboratory animals has become an essential part of research projects. To produce antibodies, investigators are confronted with a lot of complex choices, some of which may be critical for success.…”
Section: Resultsmentioning
confidence: 99%
“…Polyclonal antibodies have a complex mixture of antibodies with different specificity, affinity, and isotype. Polyclonal antibodies have the function for binding various epitopes on the surface of the inducing antigen molecule [20]. AGPT result showed the appearance of a precipitation line near the well-containing antibody which is mean weakly positive, or it is likely that the antibody titer is low [24].…”
Section: Resultsmentioning
confidence: 99%
“…Gels were then removed from glass plates and were soaked in a coomassie brilliant blue dye solution for 3 h at room temperature with stirring. Methanol and acetic acid were used to remove the dye and separated protein bands were observed on clear gels [26].…”
Section: Methodsmentioning
confidence: 99%